In fear of the spear - Hering, Marianne; Hohn, David, 1974- (Carol Stream, Illinois : Tyndale House Publishers, 2016)
Beth and Patrick time travel to 1950s and 1960s Equador where they come in contact with missionaries and the Waodani people.
"Focus on the Family, Adventures in Odyssey."
Keywords: Time travel -- Fiction; Christian life -- Fiction; Missionaries -- Fiction; Huao Indians -- Fiction; Indians of South America -- Ecuador -- Fiction; Ecuador -- History -- 1944-1984 -- Fiction